Analysis of Using Technology Podcast in the Eighth.Grade Students Listening Comprehension at UPTD SMP Negeri 5 Gunungsitoli - Angel Bertha Waruwu; Nursayani Maruao; Afore Tahir Harefa; Trisman Harefa (Universitas Syiah Kuala, 2025)
This study aims to analyze how the use of podcasts works in improving listening comprehension of grade VIII students at UPTD SMP Negeri 5 Gunungsitoli. In the digital era, audio-based learning media such as podcasts are increasingly popular and are considered effective in improving listening comprehension. This study uses a qualitative descriptive method with observation, interview, and documentation data collection techniques. The results of the study showed a significant increase in students' listening skills using podcasts. This suggests that podcasts can be an effective medium for improving students' listening comprehension. These findings support the idea that technology, if effectively integrated into education, can encourage greater engagement and improve learning outcomes. However, educators must consider overcoming existing challenges in order to fully utilize the potential of podcasts as an educational resource. Further research can explore the long-term effects and optimal strategies for integrating podcast technology into diverse learning environments.